Unstable Indicators of Temperature and Humidity in Large-Scale Special Worm Rearing Houses and the Negative Consequences of Feeding Worms in Them - Kh.E., Rakhmanova; K.A., Jumagulov (RA Journal of Applied Research, 2021)
This article reveals the information on rearing houses for silkworms. It has been observed that the larger the size of silkworm rearing houses, the more difficult it is to maintain a comfortable temperature, relative humidity and other environmental factors, and as a result, the development of silkworms, cocoon spinning processes vary, and the process implementation of agro-technical measures is disrupted. As consequently, scientifically based data show that the viability of industrial cocoons was 14.5-24.5%, and the duration of the larval period was 2-8 days.